If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) + -5 = 3x + -3 Reorder the terms: 3(1 + x) + -5 = 3x + -3 (1 * 3 + x * 3) + -5 = 3x + -3 (3 + 3x) + -5 = 3x + -3 Reorder the terms: 3 + -5 + 3x = 3x + -3 Combine like terms: 3 + -5 = -2 -2 + 3x = 3x + -3 Reorder the terms: -2 + 3x = -3 + 3x Add '-3x' to each side of the equation. -2 + 3x + -3x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 0 = -3 + 3x + -3x -2 = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 = -3 + 0 -2 = -3 Solving -2 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7-(4y-3)=4-5y | | .20x+.45(70)=45.5 | | x^2-6x-230=0 | | 1.3t+3(t+8.2)=375 | | 7t+8t=45 | | 2(2r+5)+1=5-3(3-r) | | 4(x-1)=2(x+2)-x | | 5v=-2v-3v | | -4y-12=3y+16 | | 9(x+8)=8(x-8)+x | | 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 | | 8y-2=-6y+50 | | -10=2+2.4w | | 5.8-1.4=16 | | 9(g+2)-4=7g+3(3g+8) | | 7(st)=(7s)t | | 5w+a=4.8+8w | | -(3b-15)=6(2hb+5) | | -4m-23=5 |